Lipid and blood pressure lowering effects of Mikania micrantha through enzymatic inhibition - Shafie, Nurul Husna; Ishak, Amirah Haziyah; Mohd Esa, Norhaizan; Bahari, Hasnah (Brawijaya University, 2023)
Mikania micrantha Kunth (Asteraceae) is a plant traditionally used to reduce the risk of hyperlipidemia and hypertension. There is limited information on the anti-hyperlipidemic and anti-hypertensive effects of the various M. micrantha leaves and stem extracts. This study aimed to examine the in vitro potential of different parts of M. micrantha (leaves and stem) extracts in inhibiting hyperlipidemia-related enzymes, i.e., pancreatic lipase (PL), lipoprotein lipase (LPL) and 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGR), in addition to the hypertension-related, i.e., angiotensin-I converting enzyme (ACE). This study spectrophotometrically determined the inhibitory activities of hot water, cold water, 70% ethanol, and ethyl acetate M. micrantha leaves and stem extracts against the above-said enzymes using PL, LPL, HMGR, and ACE inhibition assays. The study found that the ethanol stem (ETS) extract exhibited the highest PL inhibitory activity (IC50=4.49±2.50 μg/mL), albeit the difference was insignificant (p > 0.05) compared to orlistat (IC50=0.31±0.01 μg/mL). Meanwhile, the ethanol leaves (ETL) extract yielded the highest LPL (IC50=1.42±0.48 μg/mL) and HMGR inhibitory activity (50.12±3.44%), although the greatest ACE inhibition was observed for the hot water stem (HWS) extract (97.47±1.19%). However, the result was insignificant (p > 0.05) compared to other extracts and captopril (98.42±0.93%). In brief, the extracts generally exhibited remarkable inhibitory activity against PL, LPL, HMGR, and ACE, thus conveying the M. micrantha extracts' anti-hyperlipidemic and anti-hypertensive potentials.